Pengaruh Terapi Spiritual Emotional Freedom Technique (SEFT) terhadap Penurunan Kecemasan pada Mahasiswa Tingkat Akhir - Linta Qolbi, Lutvi; Yuliana, Nuriyah; -, Estiningtyas (STETHOSCOPE, 2023)
Abstrak Permasalahan yang sering dihadapi oleh mahasiswa tingkat akhir yang sedang menyusun tugas akhir salah satunya adalah kecemasan. Salah satu terapi yang efektif untuk mengatasi kecemasan yaitu dengan terapi Spiritual Emotional Freedom Technique. Tujuan penelitian ini adalah untuk mengetahui pengaruh terapi Spiritual Emotional Freedom Technique terhadap kecemasan. Penelitian ini menggunakan desain pre-eksperimen dengan pendekatan one group pre-post-test design. Samperl penelitian adalah mahasiswa tingkat akhir yang menyusun skripsi berjumlah 72 orang diambil dengan sebanyak 20 responden. Pengukuran menggunakan kuesioner Zung Self Rating Anxiety Scale. Intervensi diberikan sebanyak 8 kali dalam rentang waktu 4 minggu. Uji statistik menggunakan Paired Sample T-test dipatkan nilai thitung 25.812 > ttabel (df 18) 1.734 dan hasil signifikansi P-value sebesar < 0.001 (P-value < 0.05). Kesimpulan dalam penelitian ini yaitu terdapat pengaruh terapi Spiritual Emotional Freedom Technique terhadap penurunan kecemasan pada mahasiswa tingkat akhir. Kata kunci: kecemasan, terapi Spiritual Emotional Freedom Technique, mahasiswa tingkat akhir. Spiritual Emotional Freedom Technique (Seft) Therapy on Reducing Anxiety at Final-Year Students Abstract The problem that generally faced by final-year students who are writing their final project is anxiety. One of the effective therapies for dealing with anxiety is the Spiritual Emotional Freedom Technique Therapy. This therapy is included in the category of relaxation therapy that can reduce anxiety. The purpose of this research was to determine the effect of Spiritual Emotional Freedom Technique therapy on reducing anxiety. This research used a pre-experimental design with a one group pre-test and posttest design approach. The research population was final-year students who were writing thesis for Bachelor of Applied Science Health Information Management and Bachelor of Nursing STIKes Mitra Husada Karanganyar, total of 72 students by applying the sampling technique using purposive sampling, the number of samples in this research were 20 respondents. The research instrument used the Zung Self Rating Anxiety Scale questionnaire. This intervention was given 8 times for 4 weeks. After statistical tests by applying the Paired Sample T-test, the results were tcount was 25.812 > ttable (df 18) 1.734 and significant P-value was < 0.001 (P-value < 0.05), so it could be concluded that there is a significant effect of Spiritual Emotional Freedom Technique therapy on reducing anxiety for final-year students. The final-year students can apply this Spiritual Emotional Freedom Technique Therapy to conquer the anxiety they have, as a form of complementary therapy that is effective and easy to do independently. Keywords: anxiety, Spiritual Emotional Freedom Technique therapy, final-year students.